The Impact of Smoking on Sperm Quality and the DAZ Gene - Sukarjati; Nanis Choirunnisa; Nur Syamsiatul Fajar (Jurnal Penelitian Pendidikan IPA, 2024)
Indonesia's male population is mostly smokers. The chemical content in cigarettes can reduce the quality of spermatogenesis, where spermatogenesis is influenced by the DAZ gene (deleted in Azoospermia). This study aims to analyze sperm quality in light, moderate, and heavy smokers in 3 age groups and analyze the presence of the DAZ gene in heavy smokers. This study used 180 samples divided into three age groups, namely men aged 26-30 years, 31-35 years, and 36-40 years. Each age group recorded the number of cigarettes consumed per day (light, moderate, and heavy smokers) and examined the quality of sperm. While the DAZ gene analysis used 10 samples of heavy male smokers, aged 25-40 years. Sperm quality analysis was based on the WHO laboratory manual for human semen testing, while DAZ gene analysis used the PCR method. Sperm quality data were analyzed using Kruskal-Wallis, while the DAZ gene was analyzed qualitatively descriptively by analyzing electrophoresis photos. The results of this study can be concluded that daily cigarette consumption in the age group affects sperm quality and in heavy smokers, there are 10% who experience deletions in the DAZ gene. Thus cigarettes can reduce spermatozoa quality.